Environment-Dependent Variation in Gut Microbiota of an Oviparous Lizard (Calotes versicolor) - Lin Zhang; Fang Yang; Ning Li; Buddhi Dayananda (Animals, 2021)
Vertebrates maintain complex symbiotic relationships with microbiota living within their gastrointestinal tracts which reflects the ecological and evolutionary relationship between hosts and their gut microbiota. However, this understanding is limited in lizards and the spatial heterogeneity and co-occurrence patterns of gut microbiota inside the gastrointestinal tracts of a host and variations of microbial community among samples remain poorly understood. To address this issue and provide a guide for gut microbiota sampling from lizards, we investigated the bacteria in three gut locations of the oriental garden lizard (Calotes versicolor) and the data were analyzed for bacterial composition by 16S ribosomal RNA (16S rRNA) gene amplicon sequencing. We found the relative abundance of the dominant phyla exhibited an increasing trend from the small intestine to the large intestine, and phyla Firmicutes, Bacteroidetes and Proteobacteria were the three primary phyla in the gut microbiota of C. versicolor. There were a higher abundance of genus Bacteroides (Class: Bacteroidia), Coprobacillus and Eubacterium (Class: Erysipelotrichia), Parabacteroides (Family: Porphyromonadaceae) and Ruminococcus (Family: Lachnospiraceae), and Family Odoribacteraceae and Rikenellaceae in the sample from the hindgut. The secondary bile acid biosynthesis, glycosaminoglycan degradation, sphingolipid metabolism and lysosome were significantly higher in the hindgut than that in the small intestine. Taken together our results indicate variations of gut microbiota composition and metabolic pathway in different parts of the oriental garden lizard.